Stereological Assessments of Neuronal Pathology in Auditory Cortex in Schizophrenia - Parker, Emily M.; Sweet, Robert A. (Frontiers in Neuroanatomy, 2018)
It has long been known that auditory processing is disrupted in schizophrenia. More recently, postmortem studies have provided direct evidence that morphological alterations to neurons in auditory cortex are implicated in the pathophysiology of this illness, confirming previous predictions. Potential neural substrates for auditory impairment and gray matter loss in auditory cortex in schizophrenia have been identified, described, and are the focus of this review article. Pyramidal cell somal volume is reduced in auditory cortex, as are dendritic spine density and number in schizophrenia. Pyramidal cells are not lost in this region in schizophrenia, indicating that dendritic spine reductions reflect fewer spines per pyramidal cell, consistent with the reduced neuropil hypothesis of schizophrenia. Stereological methods have aided in the proper collection, reporting and interpretation of this data. Mechanistic studies exploring relationships between genetic risk for schizophrenia and altered dendrite morphology represent an important avenue for future research in order to further elucidate cellular pathology in auditory cortex in schizophrenia.